Determinants of Excess Liquidity in the Nigerian Banking System - Augustine, Ujunwa; Chinwe, Okoyeuzu; Ukpere, Wilfred I. (Journal of Reviews on Global Economics, 2018)
This study examines the determinants of excess liquidity in the Nigerian banking system using generalized autoregressive conditional heteroscedasticity (GARCH) for the period January 2008 to December 2015. The identified determinants of banking system excess liquidity are capital importation, Federation Account Allocation Committee (FAAC) distribution, exchange rate premium and policy instruments such as cash reserve ratio, special lending facility rate, Treasury bill rate and interbank rate. The empirical result revealed that the identified determinants have significant effect on banking system excess liquidity in Nigeria. Based on the findings, the study recommends that Nigerian monetary authority could rethink liquidity management in terms of developing robust strategies for mopping up the excess liquidity from the identified sources, rather than concentrating liquidating management strategy on the banking system